JURIDICAL ANALYSIS OF IMPLEMENTATION OF ASSESSMENT FOR VICTIMS OF NARCOTICS ABUSE TO REACH CERTAINTY AND LEGAL PROTECTION OF THE COMMUNITY (Research Study at the Batam City Narcotics Agency) - Antonio Kasman, Riko; Dahlan, Dahlan; Nofrial, Ramon (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This form of assessment of addicts and victims of narcotics abuse is a form of positive breakthrough in law enforcement against narcotics abusers. However, in its application, the National Police experienced problems in the assessment process for handling addicts and victims because they were influenced by various factors that hindered the achievement of the ideals as envisioned by the law. The government must make stricter and wiser regulations regarding the Narcotics Abuse Evaluation Process, all law enforcement agencies prioritize an integrated assessment process for everyone who is proven to be affected by Narcotics abuse and law enforcement officials, such as the Indonesian National Police,